Relações entre tamanho populacional, uso do habitat, dieta e predação de ninhos por Nasua nasua (Carnivora, Procyonidae) em remanescentes florestais - Ruim, Juliana Bombarda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The forest fragmentation creates mosaics of reduced and discontinuous natural habitats patches, inserted, sometimes, in inhospitable matrix. Many mammals, like large carnivores, are not able to keep their populations in small remnants, whereas others, as mesopredators, may thrive in these areas, showing overabundant populations. The coatis, Nasua narica e N. nasua, are some of species that may remain in areas substantially modified and that, in high densities, exert strong pressure on the resources consumed by them, affecting, among others, the crops around the fragments and the avifauna by preying on nests. Coatis occupy more frequently forested habitats due to, besides others reasons, the higher food availability usually provided by them. Nevertheless, agricultural matrices are commonly used as a habitat and the crops surrounding the fragments may be important items in the diet of these animals. Thus, the aim of the present work was to examine and to compare population density, habitat use, diet and the predation on ground nesting birds by Nasua nasua and some others mesopredators in two forest fragments of different sizes. The study was carried out in fragments of semideciduous forest, one of them with 680 hectares and the other with 354 hectares. The density data were collected through population census by line transects and were analyzed by the Distance program; the habitat use was recorded by walking on existent trails, observing the animals, and by the distribution of fecal samples at old-growth forest, second-growth forest and edge; the diet was verified through fecal samples and direct observations of the foraging individuals; the nest predation was studied using an experiment with artificial nests. The population density was higher in the smaller fragment as was the nest predation rate, and these seem to be related to the diminished size and isolation of the area, which make the permanence of the natural predators and the ...

A fragmentação florestal cria mosaicos de manchas de habitats naturais reduzidas e descontínuas, imersas em matriz, muitas vezes, inóspita. Muitos mamíferos, como os grandes carnívoros, não são capazes de manter suas populações em pequenos remanescentes, embora outros como alguns mesopredadores, possam prosperar nestas áreas, apresentando populações superabundantes. Os quatis, Nasua narica e N. nasua, são espécies capazes de sobreviver em áreas bastante alteradas e que em altas densidades exercem forte pressão sobre os recursos que consomem, afetando, entre outros, os plantios agrícolas no entorno dos remanescentes florestais e a avifauna ao predarem os ovos. Os quatis ocupam preferencialmente habitats florestados devido, dentre outros fatores, a maior disponibilidade de alimentos que estes geralmente oferecem, porém o uso de matrizes agrícolas é comum e os cultivos podem ser fontes importantes de itens alimentares na dieta desses animais. O objetivo deste trabalho foi analisar e comparar a densidade populacional, o uso do habitat, a dieta e a predação de ninhos de aves por Nasua nasua e alguns outros mesopredadores em dois fragmentos florestais de tamanhos diferentes. O estudo foi conduzido em fragmentos de Floresta Estacional Semidecidual, cujas áreas são respectivamente de 680 hectares e 354 hectares. Os dados de densidade foram obtidos através de censo populacional e análises pelo programa Distance; o uso do habitat foi registrado por meio de percursos em trilhas preexistentes com observações dos animais e distribuição de amostras de fezes em ambientes de floresta primária, floresta secundária e borda; a dieta foi verificada com base em amostras fecais e observações diretas dos indivíduos forrageando; o estudo sobre a predação de ninhos ocorreu através de experimentos com ninhos artificiais. Tanto a densidade populacional quanto a taxa de predação de ninhos foram mais elevadas no fragmento menor, ...
Keywords: Ecologia animal; Quati - Habitat; Quati - Alimentos; Liberação de mesopredadores; Animal ecology; Mata Atlântica